Exercise and Protein Intake: A Synergistic Approach against Sarcopenia. (21st March 2017) - Martone, Anna Maria; Marzetti, Emanuele; Calvani, Riccardo; Picca, Anna; Tosato, Matteo; Santoro, Luca; Di Giorgio, Angela; Nesci, Antonio; Sisto, Alex; Santoliquido, Angelo; Landi, Francesco
Abstract : Sarcopenia, the age-dependent loss of muscle mass and function/strength, is increasingly recognized as a major risk factor for adverse outcomes in frail older people. As such, the skeletal muscle is a relevant target for interventions aimed at preventing or postponing the occurrence of negative health-related events in late life. The association among physical inactivity, insufficient intake of energy and protein, and poor muscle health in older adults suggests that physical exercise and targeted nutritional supplementation may offer substantial therapeutic gain against sarcopenia and its negative correlates. This view is supported by observational studies as well as by small-scale clinical trials. In this review, we summarize the available evidence on the beneficial effects of behavioral interventions on sarcopenia. We also briefly describe how the knowledge gathered so far has been used to design the "Sarcopenia and Physical fRailty IN older people: multicomponenT Treatment strategies" (SPRINTT) project. The randomized clinical trial conducted within SPRINTT will provide robust evidence on the effectiveness of exercise and nutrition at preventing negative outcomes associated with sarcopenia and physical frailty.